Influenza and pneumococcal vaccinations are not associated to COVID-19 outcomes among patients admitted to a university hospital. Issue 26 (11th June 2021) - Pastorino, Roberta; Villani, Leonardo; La Milia, Daniele Ignazio; Ieraci, Roberto; Chini, Francesco; Volpe, Enrico; Barca, Alessandra; Fusco, Danilo; Laurenti, Patrizia; Ricciardi, Walter; Boccia, Stefania
Abstract: In order to reduce the burden on healthcare systems and to support differential diagnosis with COVID-19, influenza and pneumococcal vaccinations were strongly recommended during the COVID-19 pandemic, especially in vulnerable groups. However, no univocal and conclusive evidence on the relationship between influenza and pneumococcal vaccinations and COVID‐19 outcomes exists. We evaluated the association between such vaccinations, COVID-19 hospitalization, intensive care unit admissions and deaths in a cohort (N = 741) of COVID-19 patients who had access to the emergency room of a large Italian University hospital between March 1, 2020 and June 1, 2020. Results show that influenza and pneumococcal vaccinations did not affect hospitalization, intensive care unit admission and deaths in COVID-19 patients in the overall sample and in those ≥65 years. The same pattern of results was confirmed considering timing of influenza vaccine administration, vaccination type, and number of uptakes in the last five vaccination campaigns. In conclusion, our study does not support an impact of influenza and pneumococcal vaccinations on COVID-19 outcomes.